2022
DOI: 10.3390/pharmaceutics14091838
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Copper Nanoparticles in Wound Healing Process Using In Vivo and In Vitro Studies: A Systematic Review

Abstract: Chronic wounds are defined as wounds that do not heal in an orderly and timely manner through the various stages of the healing process. Copper nanoparticles are essential in dressings for wound healing because they promote angiogenesis and skin regeneration, which hasten the healing process. This systematic investigation sought to explain how copper nanoparticles affect chronic wound healing in vivo and in vitro. We realized a systematic review of original articles studying the effectiveness of copper nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 80 publications
(193 reference statements)
0
11
0
Order By: Relevance
“…Compared to traditional cotton-based hemostatic wound dressings, nanocellulose can be functionalized to promote wound healing and prevent secondary infection. Antimicrobial agents such as benzalkonium chloride, silver, and copper nanoparticles can be impregnated into the porous network of BNC’s membrane that acts as a physical barrier between the wound and the surrounding environment and facilitates the steady release of preloaded antimicrobials [ 59 , 60 , 61 , 62 , 63 ]. Furthermore, BNC can be integrated with other naturally derived materials to design next generation innovative sustainable nanomaterials.…”
Section: Sustainable Nanomaterials For Biomedical Applicationsmentioning
confidence: 99%
“…Compared to traditional cotton-based hemostatic wound dressings, nanocellulose can be functionalized to promote wound healing and prevent secondary infection. Antimicrobial agents such as benzalkonium chloride, silver, and copper nanoparticles can be impregnated into the porous network of BNC’s membrane that acts as a physical barrier between the wound and the surrounding environment and facilitates the steady release of preloaded antimicrobials [ 59 , 60 , 61 , 62 , 63 ]. Furthermore, BNC can be integrated with other naturally derived materials to design next generation innovative sustainable nanomaterials.…”
Section: Sustainable Nanomaterials For Biomedical Applicationsmentioning
confidence: 99%
“…This result is in agreement with the previous studies. Sandoval et al [5] reported that CuNPs can accelerate in vivo wound healing by stimulating angiogenesis and broblast cell proliferation. Copper nanoparticles synthesized using Allium saralicum leaves showed better wound-healing e cacy by enhancing the wound contracture, hydroxyproline, hexosamine, hexuronic acid, and brocytes content [34].…”
Section: Histopathological Ndingsmentioning
confidence: 99%
“…Additionally, copper is known to stabilize the hypoxia-inducible factor-1 (HIF-1) structure, which induces the expression and function of the vascular endothelial growth factor (VEGF) toward angiogenesis in wounds [6,35]. The hydrogel composite based on gelatin, HA, Asiatic acid, ZnO and CuO nanoparticles declined the in ammatory marker of TNF-α levels on the 7th day experiment in second degree burn wounds of rats [5]. Mirbehbahani et al [15] reported that application of Artemisia annua to the polymeric wound dressing stimulated broblast attachment and proliferation without any cytotoxicity.…”
Section: Histopathological Ndingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper has been demonstrated to have effective antibacterial properties and pro-angiogenic effects in wound healing. [24][25][26] Zinc ions are also known to contribute to antibacterial properties and wound healing. [27][28][29] Recently, copper-and zinc-based zeolitic-imidazolate frameworks (Cu@ZIF-8) have been reported to have an excellent antibacterial effect on the bone repair model.…”
Section: Introductionmentioning
confidence: 99%